(untitled) (Revista Venezolana de Salud Pública, 2018)
The objective of the research was to determine the frequency of intestinal parasitosis in children from 1 to 7 years old, according to their socio-sanitary conditions, in a population located in the Municipality of Tocuyito, Urbanización La Pocaterra. The information on the socio-sanitary conditions was obtained through a questionnaire type survey (Annex 1), to characterize these conditions were taken into account criteria for measuring the condition of life of the Inter-American Institute for Social Development.